Rancang Bangun Chatbot Budaya Berbasis Web Menggunakan Platform No-Code dengan Pendekatan User Centered Design - Rahmat Taufik R.L Bau; Hermila A; Sitti Suhada; Mohamad Reza Putra Faren Idris; Refly K. Batalipu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study addresses the need for user-friendly digital media to introduce Gorontalo’s cultural heritage to youth and tourists. We designed and developed a web-based cultural chatbot prototype (Maleo) using the Smojo platform and a User-Centered Design (UCD) approach. The method followed the UCD cycle: understanding usage context via expectation surveys, specifying functional and nonfunctional requirements, modeling interactions with use case and activity diagrams, implementing a Smojo-based prototype, and evaluating usability using the System Usability Scale (SUS). Data were collected through online questionnaires and limited user testing with local youths and visitors who had experienced Gorontalo. Results indicate a mean SUS score of 80.0 (range 62.5–100; standard deviation ≈ 12.27), placing the prototype in the excellent usability category, with clear navigation, low interaction barriers, and positive intention to reuse. The findings confirm that a UCD-driven, no-code development approach effectively produces an informative, learnable interface for local cultural contexts. Implications include enhancing onboarding, standardizing content and interoperability (via APIs), adopting multi-metric evaluations beyond SUS, and providing stakeholder analytics dashboards to strengthen the educational and promotional impacts of the platform in a sustainable manner.